Neighborhood and community factors: effects on deviant behavior and social competence - Fariña, Francisca; Arce, Ramón; Novo, Mercedes (The Spanish Journal of Psychology, 2008)
Socialization in a neighborhood and community at risk, defined in terms of violence, social alienation, school failure, and disruptive behavior, is a risk factor for the acquisition of antisocial and delinquent behavior. In order to test this hypothesis and examine the underlying mechanisms involved, 346 participants, 155 high-risk and 191 low-risk, aged 11 to 13, that is, under the age of criminal responsibility as established by the Spanish Law 5/2000 were selected. The results reveal that high-risk youngsters had higher rates of antisocial behavior and lower levels of social skills (i.e., greater tendency to externalize attribution of responsibility, fewer conflict resolution strategies, lower self esteem, and a lower degrees of emotional intelligence) in comparison to the lower-risk group. Finally, the results and implications of the study are discussed in the light of designing prevention programs.